Plasmacytoid Dendritic Cell Response to CpG ODN Correlates with CXCL16 Expression and Is Inhibited by ox-LDL. (4th November 2013) - Gursel, Mayda; Klinman, Dennis M.; Gursel, Ihsan
Abstract : Structurally distinct classes of synthetic CpG oligonucleotides (ODN) differentially activate human immune cells. K-type ODN trigger plasmacytoid dendritic cells (pDCs) to differentiate and produce TNF α . In contrast, D-type ODN stimulate large amounts of IFN α secretion from pDCs. The cell-surface receptor CXCL16 was previously shown to influence the nature and specificity of CpG ODN-induced immune activation. Here, we evaluated the expression and function of CXCL16 on pDC from healthy volunteers. We report that increased CXCL16 expression correlated with enhanced in vitro response exclusively to D-type CpG ODN. Conversely, enzymatic digestion of the receptor resulted in a decrease in IFN α production. Moreover, ox-LDL presence significantly inhibited D-ODN mediated IFN α production by pDCs. Coculture of enriched pDCs with the CXCR6 expressing Jurkat T cells decreased the activation threshold of these cells responding to D-ODN, suggesting that CXCL16/CXCR6 interaction may play an important role in modifying the response of pDCs to environmental danger signals.